2018
DOI: 10.1037/sgd0000286
|View full text |Cite
|
Sign up to set email alerts
|

Representation and erasure of bisexual people of color: A content analysis of quantitative bisexual mental health research.

Abstract: Bisexual people of color (BPOC) live with a complex intersection of identities, facing binegativity, racism, and invisibility. These issues result in a wide range of stressors that incorporate the intersecting stigmas they face in various contexts. Sexual minority research has limited applications to bisexual people, as most of the existing theories and approaches are based on research that included only lesbian and gay populations. The present study was designed to investigate the representation of BPOC in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 73 publications
2
37
0
Order By: Relevance
“…To the extent that we have developed a literature around bisexual health beyond just sexual risk behaviors, the work amassed to date, whether using probability or convenience sampling, has often been racially homogenous (Ghabrial & Ross, 2018). Additionally, transgender and gender non-conforming identities and communities are still relatively unacknowledged or accounted for in research to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the extent that we have developed a literature around bisexual health beyond just sexual risk behaviors, the work amassed to date, whether using probability or convenience sampling, has often been racially homogenous (Ghabrial & Ross, 2018). Additionally, transgender and gender non-conforming identities and communities are still relatively unacknowledged or accounted for in research to date.…”
Section: Discussionmentioning
confidence: 99%
“…What is also often lost, or invisible, is the demographic diversity that exists under the bisexual umbrella. For instance, reported rates of behavioral and self-identified bisexuality are often higher among African-American and Latinx individuals than among White individuals (Gates, 2010; Ghabrial & Ross, 2018; Herek, Norton, Allen, & Sims, 2010), with bisexuality often reported most frequently among multiracial persons as well (Herek et al, 2010). Bisexual persons live in small cities and large, in regions throughout the U.S., and are significantly more likely than gay/lesbian counterparts to be parents (Bartelt, Bowling, Dodge, & Bostwick, 2017; Herek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Flanders, Dobinson, and Logie (2015) found that many bisexual emerging adults did not feel they could be their full selves due to the lack of affirming resources within the LGBTQ+ and heterodominant cultures. Emerging adults who identify with non-binary sexual and gender identities experience invisibility and nonrepresentation of their sexual and gender identities (Farmer & Byrd, 2015;Galupo, Davis, Grynkieqicz, & Mitchell, 2014;Ghabrial & Ross, 2018).…”
Section: Discrimination and Oppression Within The Lgbtq+ Communitymentioning
confidence: 99%
“…Similar to what was found in other studies [ 1 , 3 , 15 , 22 , 23 ], bisexual women had poorer HRQoL than lesbians. There appear to be health disparities among Korean SMW: bisexuals may additionally experience bi-specific stress [ 54 , 55 , 56 , 57 , 58 ]. South Korea’s LGBT community is still growing and is characterized by a well-established majority of gay and lesbian organizations.…”
Section: Discussionmentioning
confidence: 99%